(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an in-depth exploration of phrase theory, focusing on the three primary types of phrases: coordinate, subordinate, and predicative. It outlines their defining characteristics, subtypes, and syntactic roles within sentence structures. Additionally, the article addresses the complexities of mixed phrase types, which combine elements of multiple categories, presenting challenges for syntactic analysis. By examining these phenomena, the article highlights the dynamic and fluid nature of language, emphasizing the importance of nuanced, context-dependent analysis. The discussion is aimed at enhancing understanding of sentence structure and advancing theoretical approaches to language analysis.